Competition and the location of overseas assembly - Deborah L. Swenson (University of California, Department of Economics, 2006)
How does international competition affect overseas outsourcing? While it is commonly believed that international competition enables firms to desert high cost countries in favor of low wage locations, the frequency of such responses may be reduced if the movement of outsourcing activities involves sunk costs. To put these factors in perspective, I study the production decisions of participants in the U.S. overseas assembly program (OAP). A number of interesting regularities emerge. First, the strong positive effect of prior participation on current OAP participation probabilities suggests that sunk costs influence outsourcing choices. Such production persistence is especially strong among foreign assemblers who are responsible for completing a large percentage of value-added. Second, increases in own-country costs and declines in competitor-country costs reduce participation probabilities. In addition, while these persistence and cost effects characterize all overseas assembly choices, these effects are much larger for outsourcing in developing countries. Finally, outsourcing responses appear to reflect differences in "market thickness", as cost sensitivity generally rises with competitor presence. Taken together, these observations provide empirical support for modeling approaches that feature search costs and partner availability as determinants of outsourcing decisions.
Keywords: F1; F2; 330; International Outsourcing; Production Decisions; Sunk Costs; Competition